f ( x ) = n → ∞ lim n 2 ⌊ x ⌋ + ⌊ 2 x ⌋ + ⌊ 3 x ⌋ + ⋯ + ⌊ n x ⌋
Let f ( x ) be defined as above and A be the area bounded by f ( x ) and y = x 2 . Then find ∫ 0 1 / A f ( x ) d x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nice solution.
You can also use Stolz theorem for calculating f ( x ) = 2 x and the rest would be equal to Mark Henning's solution.
Note .- ⌊ n x ⌋ = n x − { n x } ∼ n x , as n → ∞ , where { ⋅ } denotes the fractional part function . For calculating A , you need to solve the equation x 2 = 2 x ⇒ x = 0 , 2 1
By property of GIF function x − 1 ≤ ⌊ x ⌋ < x So we can now express the summation in this form of an inequality.Now we can easily evaluate the limit and it turns out that both limits are equal to be L = x / 2 .Sandwich Theorem tells us that this is our limit.The Area can be found out using A = ∫ ( f ( x ) − g ( x ) ) d x The points of intersection of 2 functions are ( 0 , 0 ) and ( 1 / 2 , 1 / 4 ) yields A = 1 / 4 8 .The final answer is thus ∫ 0 4 8 2 x d x = 5 7 6 .
Property of GIF mentioned wrong
Problem Loading...
Note Loading...
Set Loading...
A solution with the floor function incorporated...
Since ⌊ x ⌋ ≤ x < ⌊ x ⌋ + 1 for all x , it follows that x − 1 < ⌊ x ⌋ ≤ x for all x , and hence that 2 1 n ( n + 1 ) x − n = j = 1 ∑ n ( j x − 1 ) < j = 1 ∑ n ⌊ j x ⌋ ≤ j = 1 ∑ n j x = 2 1 n ( n + 1 ) x so that 2 n n + 1 x − n 1 < n 2 1 j = 1 ∑ n ⌊ j x ⌋ ≤ 2 n n + 1 x which tells us that f ( x ) = 2 1 x for all x . The area between y = f ( x ) and y = x 2 is A = ∫ 0 2 1 ( 2 1 x − x 2 ) d x = 4 8 1 and so the answer is ∫ 0 4 8 2 1 x d x = 2 4 2 = 5 7 6